Tunneling transport and spectroscopy in carbon nanotube quantum dots. - Logan, D; Galpin, MR (2009)
This paper provides a theoretical description of sequential tunneling transport and spectroscopy, in carbon nanotube quantum dots weakly tunnel coupled to metallic leads under a voltage bias. The effects of Coulomb blockade charging, spin-orbit fine structure, and orbital- and spin-Zeeman effects arising from coupling to applied magnetic fields are considered; and the dependence of the conductance upon applied gate voltage, bias voltage, and magnetic fields is determined. The work is motivated by recent experiments on ultraclean carbon nanotube dots [Kuemmeth et al., Nature (London) 452, 448 (2008)], to which comparison is made.